2019
DOI: 10.1016/j.jadohealth.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Trends in Cannabis Administration Among Adolescent Cannabis Users

Abstract: Additional work is needed to determine whether the observed adolescent cannabis administration patterns are similar across different samples and sampling methods as well as how these trends change over time with extended exposure to new products and methods. The combined knowledge gained via diverse sampling strategies will have important implications for the development of regulatory policy and prevention and intervention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
108
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(115 citation statements)
references
References 29 publications
7
108
0
Order By: Relevance
“…Vaping of marijuana and nicotine has grown in popularity among adolescents because it is erroneously perceived as "healthier" and as more discreet than smoking. 1 Vaping devices containing nicotine are also known as e-cigarettes. A vaping device consists of a metal heating element in a stainless-steel shell and a cartridge containing the vaping solution.…”
Section: Discussionmentioning
confidence: 99%
“…Vaping of marijuana and nicotine has grown in popularity among adolescents because it is erroneously perceived as "healthier" and as more discreet than smoking. 1 Vaping devices containing nicotine are also known as e-cigarettes. A vaping device consists of a metal heating element in a stainless-steel shell and a cartridge containing the vaping solution.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 3% of adolescent cannabis users across the United States reported edible use as their first method of cannabis administration, whereas 65% reported it as the second (Knapp et al, 2018). Of those who initiated edible use after smoking cannabis, 65% did so within a week to a year after first smoking (Knapp et al, 2018).…”
Section: Initiation Of Usementioning
confidence: 99%
“…Approximately 3% of adolescent cannabis users across the United States reported edible use as their first method of cannabis administration, whereas 65% reported it as the second (Knapp et al, 2018). Of those who initiated edible use after smoking cannabis, 65% did so within a week to a year after first smoking (Knapp et al, 2018). The impact of medical cannabis laws on initiation of edible use was examined by Borodovsky et al, (2016) who found no significant difference in the age of onset of edible use between medical cannabis law states and nonmedical cannabis law states in the United States.…”
Section: Initiation Of Usementioning
confidence: 99%
See 1 more Smart Citation
“…Methods of use include oral ingestion, vaping, or smoking in rolled cigarettes ("joints"), water pipes ("bongs"), or hollowed-out cigars ("blunts"; Johnston et al, 2019). A recent national survey of adolescents ages 14-18 years revealed that smoking cannabis was the most frequent and consistent route of use (Knapp et al, 2019). The significant increase in the potency of cannabis over the past two decades (4% in 1995 to 12% in 2014) poses a higher risk for use among youth 1 (ElSohly et al, 2016) The sociopolitical landscape and public discourse about cannabis has evolved over the past two decades; as of publication, 34 states plus the District of Columbia, Guam, Puerto Rico and US Virgin Islands have enacted laws for medical marijuana use and 9 states plus the District of Columbia have legalized small amounts of cannabis for adult recreational use (National Council of State Legislatures, 2019).…”
mentioning
confidence: 99%